2010
DOI: 10.4149/neo_2010_06_578
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and treatment outcome in 1,516 adult patients with de novo and secondary acute myeloid leukemia in 1999–2009 in 5 hematology intensive care centers in the Czech Republic

Abstract: Acute myeloid leukemia (AML) is a severe condition with a high mortality. When making decisions about the optimal tailor-made therapy, numerous prognostic factors are considered. The study represents a detailed analysis of the role of these factors and treatment outcomes based on a long-term follow-up of patients treated in 5 hematology intensive care centers in the Czech Republic.The studied group comprised 1,188 patients with de novo AML and 328 patients with secondary AML. The latter were significantly olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…8 This is largely due to the high percentage of secondary AML associated with multidrug resistance (MDR) mechanisms: up to 70% of secondary AML patients show overexpression of P-glycoprotein (Pgp) or other MDR mechanisms. 9 The genetic changes in leukemic blasts make them ineffective at generating mature red blood cells, neutrophils, monocytes, and platelets. In addition, these AML blasts also inhibit normal blasts from differentiating into mature progeny.…”
Section: Introductionmentioning
confidence: 99%
“…8 This is largely due to the high percentage of secondary AML associated with multidrug resistance (MDR) mechanisms: up to 70% of secondary AML patients show overexpression of P-glycoprotein (Pgp) or other MDR mechanisms. 9 The genetic changes in leukemic blasts make them ineffective at generating mature red blood cells, neutrophils, monocytes, and platelets. In addition, these AML blasts also inhibit normal blasts from differentiating into mature progeny.…”
Section: Introductionmentioning
confidence: 99%
“…In a long-term follow-up from five hematological intensive care centers, age was one of the most important prognostic factors for overall AML patients [23] , [24] . Our data from 152 elderly patients also confirmed that older age predicts shorter OS and RFS and lower CR rate in elderly AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…These detected chromosomal aberrations are the most important tool to classify patients at their initial diagnosis and to divide them into favorable, intermediate and unfavorable subgroups. The age of the patient is also an important prognostic factor (Juliusson et al, 2009;Szotkowski et al, 2010). However, approximately 45% of adult patients with AML have normal karyotype (cytogenetically normal /CN/-AML patients) and are usually classified as an intermediate risk group (Mrozek et al, 2007;Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%